EXPLORING THE USE OF ANIMATED TRAPEZIUM IN TEACHING ENGLISH DIPHTHONGS AT SENIOR JUNIOR HIGH SCHOOL STUDENTS - Rahman, Arif (University of Kuningan, 2024)
The main purpose of this study was to examine Animated Trapezium to teach the English Diphthongs as one of some important and complicated aspects, the articulation of diphthongs is often treated as the “stepchild of language learning aspects” compared to that of grammar and vocabulary. Further than that, as one of the phonetic systems, articulating diphthongs is not usually taught explicitly in secondary schools. Indeed, articulating diphthongs is often problematic for the EFL/ESL teachers as well. This study found that most (if not all) English teachers adopted some approaches by relying on materials that, as a matter of fact, lack grounding but expect good results. In Indonesia, particularly in West Nusa Tenggara for the secondary school level, articulating diphthongs is one most difficult parts of the English sound systems to learn. It is commonly known that the difficulties are caused by the fact that in the Indonesian language, diphthongs are usually (if not always) articulated by monophthongize. As such, in trying to articulate the English diphthongs, secondary school students also tend to monophthongize them. Designed by giving animation to the common English vowel trapezium, this paper is intended to discuss how this ‘Animated Trapezium’ can be used by English teachers as the medium of teaching and how this medium can help students easier to understand and practice articulating the English diphthongs.